Non-clinical interventions to prevent postpartum haemorrhage and improve its management: A systematic review. (September 2019) - Gaucher, Laurent; Occelli, Pauline; Deneux-Tharaux, Catherine; Colin, Cyrille; Gaucherand, Pascal; Touzet, Sandrine; Dupont, Corinne
Abstract: Postpartum haemorrhages (PPHs) account for around 200 deaths per year in the developed regions of the world. However, the efficacy of pharmacological and clinical interventions to prevent or manage PPHs is well established. Our objective was to determine the effectiveness of non-clinical interventions targeting healthcare professionals, organisations or facilities in preventing PPH or improving its management. We conducted a systematic review using the PRISMA four-step model. The MEDLINE and Cochrane databases were searched up to March 2019. Inclusion criteria were interventional studies, published in English of French language, aiming to reduce PPH outcomes for women in hospitals, regardless of study design. The studies' methodological quality was assessed according to the Cochrane EPOC criteria. We found 32 studies that met the inclusion criteria. None met all the methodological quality criteria. Six types of non-clinical interventions were identified: guideline dissemination, audit with feedback, simulation, training, clinical pathway and multifaceted interventions. Eleven studies reported a significant reduction in PPH rates and/or its complications, five studies reported a significant increase and 16 studies no significant results. The heterogeneity of the studies prevents us from identifying an effective non-clinical intervention in reducing PPH rates.